Case report: transnasal sphenopalatine ganglion block for the treatment of postdural puncture headache - a successful avoidance of epidural blood patch / Siti Aznida Ab Karim ... [et al.] - Ab Karim, Siti Aznida; Mustapha Kamar, Rusnaini; Kassim, Zawiah; Zakariah, Mohd Fahmi (Faculty of Medicine, 2023)
Postdural puncture headache (PDPH) is a known complication following neuraxial anaesthesia and inadvertent dural puncture in obstetric patients. Epidural blood patch (EBP) is widely recognized as the gold standard in the treatment of PDPH. However, it is invasive and is associated with serious complications such as meningitis, infection, cauda equina syndrome, and risk of creating second inadvertent dural puncture. Topical transnasal sphenopalatine ganglion (SPG) block has recently emerged as a non-invasive treatment of PDPH. We describe our first experience in performing transnasal SPG block using lignocaine and dexamethasone mixture in a patient who presented with recurrent PDPH after failed conservative management.